Ultrasound Microbubbles for Diagnosis and Treatment of Cardiovascular Diseases - Rix, Anne; Curaj, Adelina; Liehn, Elisa; Kiessling, Fabian (Seminars in Thrombosis and Hemostasis, 2020)
Ultrasound (US) imaging of heart and major arteries and veins is among the most frequently used diagnostic techniques applied in humans. Conventional cardiovascular US sessions include anatomical B-mode and functional M-, pulsed-wave- and Doppler mode, which have their limitations in both precise cardiac chambers' delineation and small vessel imaging. The introduction of contrast-enhanced US, employing microbubble suspensions as contrast agent, has enabled a better delineation of heart chambers, the visualization of myocardial microvasculature, and the atherosclerotic plaque neovascularization. Moreover, specific disease-related molecular tracers have been developed by modifying the microbubbles with targeting ligands directed to biological markers exposed to the luminal side of the blood vessels. Microbubble functionalization has enabled in vivo molecular US imaging of various stages of atherosclerosis, from plaque initiation to plaque vulnerability, and neointima formation following revascularization procedures. Furthermore, oscillating microbubbles have been used to mechanically dissolve thrombus material and may act as carriers of drugs and nucleic acids that are released locally by US pulses. This review article summarizes recent advances in functional and molecular US images and discusses therapeutic applications of microbubbles. The addressed topics include an overview on microbubble formats, microbubble detection methods, molecular targets of cardiovascular diseases, and the use of microbubbles for thrombolysis and drug delivery.
Keywords: cardiovascular; microbubbles; molecular imaging; therapeutic ultrasound; ultrasound